Situation report on Nepal’s agrifood systems: January 2024 - Palikhe, A.; Adhikari, M.; Gupta, S.; Maharjan, N.K.; Kumar, Avinash; Minot, Nicholas; Koirala, P.; Krupnik, Timothy J. (CSISA, 2024)
From mid-November to December 2023, Nepal witnessed the lowest Consumer Price Inflation (CPI) in 12 months. The average year-on-year CPI registered a decline of 4.9 percent, which was primarily propelled by a 3.1 percent fall in food and beverage prices. This decline will have positive implications on poor rural and urban households allowing them to access and afford more food and nutrients.